An ultra-thin compact polarization-independent hexa-band metamaterial absorber - Munaga P.; Bhattacharyya S.; Ghosh S.; Srivastava K.V. (My University, 2025)
In this paper, an ultra-thin compact hexa-band metamaterial absorber has been presented using single layer of dielectric. The proposed design is polarization independent in nature owing to its fourfold symmetry and exhibits high angular stability up to 60° angles of incidences for both TE and TM polarizations. The structure is ultrathin in nature with 2 mm thickness, which corresponds to λ/11.4 (λ is the operating wavelength with respect to the highest frequency of absorption). Six distinct absorption frequencies are obtained from the design, which can be distributed among three regions, namely lower band, middle band and higher band; each region consists of two closely spaced frequencies. Thereafter, the dimensions of the proposed structure are adjusted in such a way that bandwidth enhancement occurs at each region separately. Simultaneous bandwidth enhancements at middle and higher bands have also been achieved by proper optimization of the geometrical parameters. The structure with simultaneous bandwidth enhancements at X- and Ku-bands is later fabricated and the experimental absorptivity response is in agreement with the simulated one. © 2018, Springer-Verlag GmbH Germany, part of Springer Nature.